The Stress Contrast Effect of Laminated Shaly-Sand Reservoir to Multistage Hydraulic Fracturing Design for Optimizing the Horizontal Well Productivity in K Field - Joshua Reynaldi, Kevin
The mature field K has been produced since 1986 and is characterized by heterogeneous reservoir formations. K-1 is one of the formations that is considered to be developed further by the operator company. Based on well logging analysis, K-1 consisted of sandstone formation with low resistivity and low permeability. However, according to petrography analysis, it was confirmed that the formation rock was sandstone dominated with shale layered-thin section. With the existing three production wells, the cumulative production from formation K-1 can only cover the ultimate recovery up to 3% of the total hydrocarbon in place. To increase the recovery of this formation, horizontal well with multistage hydraulic fracturing method was considered to be applied in this shaly-sand reservoir. The main challenge to perform horizontal well hydraulic fracturing is to make sure the fracture propagation can bypass the vertical permeability barrier by shale layers in the reservoir to be able to enhance the recovery throughout all layers. This challenge is dominantly bounded by the stress-contrast property between shale and sand layers that will mainly affect the propagation of fracture. Thus, the stress-contrast property should be well considered during the hydraulic fracturing design to be able to create fractures with the desired geometry. This study will show that the design that put consent on stress contrast will have an increase in dimensionless conductivity and significant increase in effective permeability and oil rate. The other parameter contributing to fracture propagation during hydraulic fracturing is the connection between fractures during the growth. One fracture growth can restrict the other fracture growth and lead to early screenout, resulting in a non-optimum vertical growth. Therefore, hydrajetting will be overlooked as it will help preventing the overlaying fracture propagation and generate the result which is 4 times longer fracture height compared to common multislot operation. This paper provides a comprehensive study in designing the horizontal well multistage hydraulic fracturing with consideration to the stress-contrast property of shaly-sand layers. Multistage hydraulic fracturing is proven to be the optimum development scenario based on technical and economical evaluation for maximizing recovery of reservoir K-1. This scenario generates best drainage performance as lateral drainage is improved accordingly with bypassed vertical permeability barrier, which recovery attained is 37.96% improvement from current deviated fractured well existing. Moreover, multistage hydraulic fracturing gives highest IRR, biggest NPV for contractor and government, fastest payout time, and most interesting value of profitability index.